The Influence of Gold Price Fluctuations, Income, and Financial Management on Investment Decisions in Gold Savings with Investment Knowledge as a Moderating Variable - Tina Ardianti; Dedi Hariyanto; Heni safitri (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the influence of gold prices, income, and financial management on the decision to invest in gold savings among employees of PT Bank Syariah Indonesia, Tbk in Pontianak and Kubu Raya, with investor knowledge serving as a moderating variable. An associative research design was employed, with data collected from 151 employees using a saturated sampling technique. The data were analyzed using multiple linear regression and moderated regression analysis (MRA). The results of the study indicate that gold prices have a significant effect on investment decisions, whereas income and financial management do not have a significant impact. Investor knowledge was found to moderate the relationship between gold price fluctuations and investment decisions. These findings highlight the importance of understanding gold price movements and effective financial management when making investment decisions. The study is expected to contribute to the enhancement of financial literacy among employees